REVERSE ENGINEERING OF COMPLEX SHAPED PARTS - Sorokovyi, О.; Shokalo, A. (Academic journal Industrial Machine Building Civil Engineering, 2017)
Modern automated design of complex shaped parts using CAD/CAM/CAE software faces the task of creating a virtual 3D-model of an existing physical object, without reference to the source documentary producer. This work is dedicated to the practical application of reversible designing of technology elements used in extreme downhill biking. Significant load leads to destruction of some parts of the equipment, but replacement of a unit is economically disadvantageous. Simulation of the idler lower pulley wheel of rear derailleur and creation of attachment to the protective helmet are described in the paper. The aim of the present research is practical application of the knowledge, obtained in the classroom with computer 3D-design of complex shaped parts, using a modern technology of reverse engineering (modeling) by means of PowerSHAPE 2015 (Delcam Ltd, UK) and Autodesk Fusion 360 (USA) software. The work will be presented to the international student competition Delcam 2016 and was awarded the second prize of the International 3D Modeling Competition 2016 at Pavel Sukhoi State Technical University of Gomel, Belarus.